EPIGRAPHY OF THE XII–XVIII CENTURIES FROM THE AGUL VILLAGE OF RICHA (NEW DATA) - Zakariaev, Zamir Sahbanovic; Gasanov, Magomedrasid Anvarbekovic (History, Archeology and Ethnography of the Caucasus, 2020)
In the abundance of epigraphic monuments and their historical and cultural significance, the ancient Aghul village of Richa stands out among other mountain villages and auls of Dagestan. The aim of this paper is to present the results of the study of Arabic inscriptions found in the village of Richa. More than twenty previously unknown inscriptions in various genres of epigraphy – construction, ownership and vital records, epitaphs and religious texts – have been for the first time introduced into modern linguistics. Notable among them are the most ancient monuments of Arabic Kufic writings, paleographically dated the XI-XII centuries, which testifies to the early popularization of Islam in Richa. In addition, the authors propose a new way of reading some of the Richa inscriptions that are already known to science. The presence of Kufic inscriptions on the walls of three mosques in Richa, as well as Naskh inscriptions dated 1242 on the walls of another mosque, suggest that mosques had existed in Richa even before the Mongols came here in 1239. Researchers have revealed the oldest dated epitaph in Richa (1300–01) in which the term alim (scholar) was used for the first time in the epigraphy of Dagestan. New valuable data have been obtained on the history of construction and reconstruction of Muslim places of worship, mausoleums, sanctuaries, and public buildings. Names of many local craftsmen, carvers and calligraphers have become known. The inscriptions contain valuable information on representatives of the medieval religious elites and Sufi figures. The rich social and professional terminology used in the newly identified Richa inscriptions is also of interest: sultan, shaykh, pir, murid, alim, qadi, ustad (usta), qatib, nakir, sahib, gulam, kavha. Translations of the texts are accompanied by scientific comments.